Modern Scientific Approaches on Defining an Administrative Offense - O. V. Panaciuk (Law and Safety)
The correlation of the terms of “administrative misdemeanor” and “administrative offense” has been characterized; the legal definition of “illegal act” as the main component of the content of an administrative misdemeanor has been analyzed; the main legislative features of an administrative misdemeanor have been classified, each of them has been characterized.